Intermittent-vacuum assisted thermophilic co-digestion of corn stover and liquid swine manure: Salinity inhibition. (January 2019) - Zhang, Renchuan; Anderson, Erik; Chen, Paul; Addy, Min; Cheng, Yanling; Wang, Lu; Liu, Yuhuan; Ruan, Roger
Highlights: High salinity was a more serious inhibition than high concentration ammonia in TAD. Half the CH4 production was loss in TAD, while the salinity increased from 2% to 4%. Methanogenesis was completely inhibited at 8% salinity in TAD. Butyrate was a indicator of the non-salinity inhibited methanogenesis in TAD. Abstract: In this study, the effects of Intermittent-Vacuum Stripping (IVS) on activities of methanogenesis in co-digestion of corn stover with liquid swine manure (LSM + CS) under thermophilic anaerobic digestion (TAD) conditions were evaluated. A 65% methanogenesis activity inhibition was observed in pretreated LSM plus corn stover (pLSM + CS), while 60 and 165 mL/L/day CH4 productions were achieved in pLSM + CS and LSM + CS, respectively. The high salinity condition (5.28%) after IVS pretreatment was considered the primary inhibitor in pLSM + CS, while the ammonia (≤600 mg/L), C:N ratio (15.52) and volatile solid loading rate (3 g/kg −1 ·day −1 ) didn't show a negative effect on CH4 production. When salinities were increased from 2% to 4% and 8%, 50% and 100% inhibition were observed respectively. The butyrate accumulation was a potential indicator of the non-salinity-inhibition status for methanogenesis in TAD.